UTILIZING YOUTUBE VIDEO TO ENHANCE STUDENT’S SPEAKING SKILL - Rida Aisyah Fadhillah; Yanti Rusmiati (Center for Research and Community Service (LPPM) University of Abulyatama, 2022)
The researcher discovered several goals, including determining the effectiveness of using YouTube videos to improve students speaking skills and determining the strengths and weaknesses of using YouTube videos to improve students speaking skills. The research was conducted in a classroom action research. This study used 31 students as a sample who were at SMP Walisongo Bekasi. To collect the data, the researcher used observation, interview, and the speaking test. The study reports that the use of youtube videos can improve the students speaking skills. The result obtained from the pre-test value is 64,61, cycle 1 is 69,96 with results that have not met the target, then continued with cycle II which achieved success with a value of 78,19. The advantages of using YouTube videos are students feel enjoyable when watching and they feel they get the idea to speak from the original speaker. The disadvantage of using YouTube videos is that students get bored easily when they see YouTube for too long, it also makes them feel they have thrown away internet pulses. Learning to speak using YouTube still has its drawbacks.